Ndibeer and Ned Ride Again: Excursions in and around the Fifth Province - Partridge, Karen Mary (Murmurations: Journal of Transformative Systemic Practice, 2021)
This article tells a dialogical story and describes a process of mutual learning and embodiment over the course of a long therapeutic relationship. The article maps the development of relationship, between my inner voices, my supervisors and those of my client, where stories of self and other are articulated, elaborated and externalised using the metaphor of a "bundle of treasures". A self-reflexive process of personal and professional mapping, using the hierarchical model of the Coordinated Management of Meaning, is described. In a recursive and isomorphic process, supervisory and therapeutic conversations further elaborate these stories, and through joint action, enable the creation of a liminal, reflexive space, a Fifth Province position, a cauldron of creativity where practice-based theory can develop. This process will be illustrated as it arises in the story of relationship and the process of therapy, so this narrative invites the reader to become an active participant in a never-ending process where theory becomes a live metaphor in the quest for being human